4-Chloro-2,6-dinitrophenol - Ng, S.W. (International Union of Crystallography, 2010)
The aromatic ring of the title compound, C6H3ClN2O5, is almost planar (r.m.s. deviation = 0.007 angstrom); one nitro substituent is nearly coplanar with the ring [dihedral angle = 3(1)degrees], whereas the other is twisted [dihedral angle = 36 (1)degrees]. The phenol OH group is intramolecularly hydrogen bonded to the nitro group that is coplanar with the ring, generating an S(6) graph-set motif.